2011
DOI: 10.1371/journal.pone.0018932
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Activates Peroxisome Proliferator Activated Receptor-γ in CHO Cells That Over-Express Glycerol 3-Phosphate Acyltransferase-1

Abstract: Lysophosphatidic acid (LPA) is an agonist for peroxisome proliferator activated receptor-γ (PPARγ). Although glycerol-3-phosphate acyltransferase-1 (GPAT1) esterifies glycerol-3-phosphate to form LPA, an intermediate in the de novo synthesis of glycerolipids, it has been assumed that LPA synthesized by this route does not have a signaling role. The availability of Chinese Hamster Ovary (CHO) cells that stably overexpress GPAT1, allowed us to analyze PPARγ activation in the presence of LPA produced as an intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Loss of SEIPIN function can change the quantity and/or distribution of certain lipids, such as PA (21). PAs could inhibit adipocyte differentiation by serving as highaffinity PPAR-g antagonists (31). In support of this hypothesis, Rosi treatment significantly improved a number of metabolic profiles of the ASKO mice and also rescued the adipogenic defect in Seipin 2/2 mouse embryonic fibroblasts, as shown recently (Fig.…”
Section: Seipin and Ppar-gsupporting
confidence: 74%
“…Loss of SEIPIN function can change the quantity and/or distribution of certain lipids, such as PA (21). PAs could inhibit adipocyte differentiation by serving as highaffinity PPAR-g antagonists (31). In support of this hypothesis, Rosi treatment significantly improved a number of metabolic profiles of the ASKO mice and also rescued the adipogenic defect in Seipin 2/2 mouse embryonic fibroblasts, as shown recently (Fig.…”
Section: Seipin and Ppar-gsupporting
confidence: 74%
“…PA has previously been shown to accumulate in tissues of lipin-1-deficient mice and contribute to impaired adipose tissue development and peripheral neuropathy in those animals (13,14). Recent studies have implicated tissue PA content in several aspects of metabolic homeostasis, including reductions in the expression and activation of peroxisome proliferator-activated receptor-γ (14,34), activation of ERK signaling (13), inhibition of mammalian target of rapamycin complex 2 (35), inflammatory signaling (36), and others (reviewed in ref. 37).…”
Section: Lipin-1 and Lipin-2 Proteins Appear To Form Heterodimers (33)mentioning
confidence: 99%
“…In addition to their roles as building blocks for TAG biosynthesis, the intermediates in the glycerol phosphate pathway are bioactive lipids. A recent study on the rate-limiting enzyme of the pathway, GPAT1, demonstrated that the product of this enzyme (lysophosphatidic acid) increases PPAR␥ activity in Chinese hamster ovary cells, as assessed by a luciferase reporter assay (19). In contrast, overexpression of AGPAT2, the subsequent enzyme in the glycerolipid pathway, which utilizes lysophosphatidic acid as a substrate and converts it to PA, attenuated PPAR␥ activity.…”
Section: Lipin-1 Modulates Phosphatidate Levels During Adipogenesismentioning
confidence: 99%
“…PPAR␥ activity can be modulated by endogenous lipid ligands, including activation by oxidized fatty acids, and inhibition of PPAR␥ activity by cyclic phosphatidic acid (10,16,17). In addition, recent evidence indicates that enzymes of the glycerol 3-phosphate pathway for triglyceride biosynthesis may have roles in PPAR␥ activation and/or adipogenic gene expression (18,19). The activity of glycerol-3-phosphate acyltransferases, acylglycerol acyltransferases, and the lipin phosphatidate phosphatases (PAP) sequentially convert glycerol 3-phosphate to lysophosphatidic acid (glycerol-3-phosphate acyltransferases), then to phosphatidic acid (acylglycerol acyltransferases), and to diacylglycerol (lipins) (reviewed in Refs.…”
mentioning
confidence: 99%